C–H-Functionalization logic guides the synthesis of a carbacyclopamine analog - Rabe, Sebastian; Moschner, Johann; Bantzi, Marina; Heretsch, Philipp; Giannis, Athanassios (Beilstein Journal of Organic Chemistry, 2014)
The chemical synthesis of carbacyclopamine analog 2, a cyclopamine analog with an all-carbon E-ring, is reported. The use of C–H-functionalization logic and further metal-catalyzed transformations allows for a concise entry to this new class of acid-stable cyclopamine analogs.
Keywords: cyclopamine; C–H-functionalization; hedgehog signaling pathway; natural products; steroidal alkaloids